2004
DOI: 10.1074/jbc.m311376200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the E2 Transactivation Domain of Human Papillomavirus Type 11 Bound to a Protein Interaction Inhibitor

Abstract: Interaction between the E2 protein and E1 helicase of human papillomaviruses (HPVs) is essential for the initiation of viral DNA replication. We recently described a series of small molecules that bind to the N-terminal transactivation domain (TAD) of HPV type 11 E2 and inhibits its interaction with E1 in vitro and in cellular assays. Here we report the crystal structures of both the HPV11 TAD and of a complex between this domain and an inhibitor, at 2.5-and 2.4-Å resolution, respectively. The HPV11 TAD struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 48 publications
2
70
0
Order By: Relevance
“…1B), as opposed to the outer surface, which mediates E2 · E2 interactions in the free HPV16 and HPV18 E2 structures. The absence of dimerized E2 molecules in the E1 · E2 complex, as well as in the uncomplexed HPV11 E2 structure (Wang et al 2004), supports the notion that the dimerization of E2-AD observed in some crystal forms may be fortuitous. For E2-dependent DNA replication in vivo, a single E2-binding site is sufficient in transient assays (Russell and Botchan 1995); similarly, an E2 dimer containing a single activation domain functions as wild type in vitro (Lim et al 1998).…”
Section: Structure Of the E1 · E2 Complexsupporting
confidence: 57%
“…1B), as opposed to the outer surface, which mediates E2 · E2 interactions in the free HPV16 and HPV18 E2 structures. The absence of dimerized E2 molecules in the E1 · E2 complex, as well as in the uncomplexed HPV11 E2 structure (Wang et al 2004), supports the notion that the dimerization of E2-AD observed in some crystal forms may be fortuitous. For E2-dependent DNA replication in vivo, a single E2-binding site is sufficient in transient assays (Russell and Botchan 1995); similarly, an E2 dimer containing a single activation domain functions as wild type in vitro (Lim et al 1998).…”
Section: Structure Of the E1 · E2 Complexsupporting
confidence: 57%
“…Such interdimer interactions and DNA loops would allow transcription factors that are bound near E2 at distal sites to be brought into the proximity of a transcription initiation site. However, recent reports of the structure of the HPV11 E2 transactivation domain (56) or HPV18 E2 transactivation domain (1) found no evidence of self-interaction or dimerization through the transactivation domain, so it is unclear whether the BPV1 E2 protein can also participate in interdimer interactions. Notably, the EpsteinBarr virus EBNA1 protein, which has analogous genome maintenance and segregation functions to those of E2 and associates with mitotic chromosomes, also mediates the looping of DNA (25,(34)(35)(36)59).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of this dimerization has not been determined, it seemed to be of major importance for protein function, as most mutations in HPV-16 E2 that compromise transactivation without affecting replication were found to map in the dimerization interface (28). Although the HPV-11 E2 protein crystal structure has since been determined to be monomeric, probably due to different crystallization conditions (45), dimer formation in the HPV-16 E2 TAD was verified in solution, using biophysical techniques (5).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the intact E2 protein closely resembles that of other mammalian transcription factors, consisting of a DNA-binding/dimerization domain (DBD) connected by a flexible linker to a multiple-protein-binding transactivation domain (TAD). The three-dimensional structures of the C-terminal DBD (11,16,17) and N-terminal TAD (1,5,15,30,45) of several E2 proteins have been reported, both alone and in complex, revealing a tight dimer of the DBD bound to DNA and a characteristic L-shaped TAD structure. In the case of HPV-16, two TAD domains form a dimer; this additional dimerization interface has been proposed to link two E2 dimers bound via the DBD to two distant E2BS within the URR (5).…”
mentioning
confidence: 99%